(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
It is no secret that our President is currently implementing a series of measures to encourage students to study foreign languages, particularly English. As a result, the author goes into great length in this essay about the value of learning other languages and the methods of learning English, as well as the capacity to use modern technologies in the language teaching process.